If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + 3x = 10 Solving -1 + 3x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 3x = 10 + 1 Combine like terms: -1 + 1 = 0 0 + 3x = 10 + 1 3x = 10 + 1 Combine like terms: 10 + 1 = 11 3x = 11 Divide each side by '3'. x = 3.666666667 Simplifying x = 3.666666667
| 1ov=60 | | y+y=5 | | 14q+14q+3p-1q= | | 9x-1/4y=5 | | 1/2w +2 = 4 | | 52-9=16 | | 3x^2+18x+81=25 | | ((a+4)/3a)-((2-4a)/6a) | | (a+4)/3a-(2-4a)/6a | | -16x^2-22x+100=62 | | (a+4)/(3*a)-(2-4*a)/(6*a) | | 14a^2/2a-8a | | 5x+20=100 | | 2n+8n-19=81 | | (-2y)-(4x)=20 | | 3x^2-4=4 | | 2x+25=25 | | x-0.6x=32 | | sqrt(2x)+13=5 | | x+2x+14=166 | | x-6=2/3+12 | | 5x-48+7x=-12 | | 9m+19m=84 | | 6x-6=0.5x+38 | | 12x-5=30x+1 | | 5x-48+7x=-21 | | 1/7*y=-15 | | 9-72/3 | | (3x^2-13x-10)/(x-5) | | y/7=-15 | | -0.43=0.03x+0.15 | | 2y=10x |